2014
DOI: 10.2337/db14-0006
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Stimulates Carbohydrate Oxidation and Protects Against Metabolic Disorders Induced by High-Fat Diets

Abstract: Excessive dietary fat intake causes systemic metabolic toxicity, manifested in weight gain, hyperglycemia, and insulin resistance. In addition, carbohydrate utilization as a fuel is substantially inhibited. Correction or reversal of these effects during high-fat diet (HFD) intake is of exceptional interest in light of widespread occurrence of diet-associated metabolic disorders in global human populations. Here we report that mangiferin (MGF), a natural compound (the predominant constituent of Mangifera indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 49 publications
5
74
0
Order By: Relevance
“…It has been reported that MGF may protect against hyperglycemia, hyperinsulinemia, and insulin resistance in high-fat diet-fed mice [51], in diabetic insulin-resistant rats [37], and in overweight patients [17], as well as against accelerated glucose uptake and utilization in cultured adipocytes and myotubes [51, 52]. However, MGF did not significantly affect fatty acid oxidation even under a high-fat dietary challenge [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that MGF may protect against hyperglycemia, hyperinsulinemia, and insulin resistance in high-fat diet-fed mice [51], in diabetic insulin-resistant rats [37], and in overweight patients [17], as well as against accelerated glucose uptake and utilization in cultured adipocytes and myotubes [51, 52]. However, MGF did not significantly affect fatty acid oxidation even under a high-fat dietary challenge [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, MGF did not significantly affect fatty acid oxidation even under a high-fat dietary challenge [51]. Other major phenolic compounds found in mango fruit powder Careless TM , such as gallic acid or rutin [18], have been reported to up-regulate genes involved in lipolysis and fatty acid oxidation in adipocytes [53].…”
Section: Discussionmentioning
confidence: 99%
“…Pasha Apontes et.al. reported that MGF can improve glucose metabolism to prevent against metabolism disorder induced by HFD, an effect that is similar to the activation of AMPK thereby ameliorating metabolism dysfunction [21]. In conclusion, the mechanism of MGF attenuating endothelial dysfunction is closely related to the activation of AMPK which inhibits ER stress.…”
Section: Discussionmentioning
confidence: 80%
“…Mangiferin (MGF) is one of the main constituents in common anemarrhena, a traditional medicine, for treating diabetes [19][20][21]. Recently, it has been reported that MGF can attenuate high-fat diet (HFD)-induced metabolism syndrome through activating AMP-actived protein Kinase (AMPK) for abnormal lipid metabolism regulation, anti-inflammation, and insulin resistance improvement [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mangiferin and the related herbs have been demonstrated to have antidiabetic activity in rodents (Ichiki et al, 1998;Li et al, 2004;Li et al, 2008;Muruganandan et al, 2005;Akase et al, 2011;Apontes et al, 2014;Han et al, 2015). Furthermore, it has been recently reported that mangiferin supplementation improves insulin resistance index in overweight patients (Na et al, 2015).…”
Section: Introductionmentioning
confidence: 99%